ASSESSMENT OF SOCIAL ATTITUDES DURING ONLINE LEARNING USING WHATSSAPP - Ristasari Oktavia; Nurul Khotimah; Ade Pratama Putra; Ahmad Walid (LPPM Universitas Negeri Jakarta, 2021)
Abstrack: The purpose of this research is to obtain a description of students' social attitudes in learning activities on WhatsApp media. This research is a quantitative study using a survey method. The sample that the researchers took themselves were tadris science students class 2018. The instrument provided was a questionnaire distributed in the form of google form. This is done in order to make it easier for objects to access them. The results of research that have been carried out on the social attitudes of the 2018 science tadris study program students which include honesty, discipline, caring for each other, responsibility and courtesy can be categorized as quite good.